PENGARUH FAKTOR EKONOMI, SOSIAL, DAN TEKNIS TERHADAP PENGGUNAAN PINJAMAN ONLINE DI KALANGAN MAHASISWA - Dewanto, Prima Adi; Yanti, Harti Budi (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2025)
This study analyzes the impact of economic, social, and technical factors on online loan usage among university students in Indonesia. Online loans are increasingly popular for addressing educational and living expenses but pose risks such as financial dependency and repayment issues. Using a quantitative survey method, data were collected from 300 students across various universities. Key findings reveal that economic factors (family income and living expenses) have the strongest influence, followed by social (peer influence and social norms) and technical factors (ease of access and approval speed). While online loans provide quick financial solutions, their risks highlight the need for better financial literacy among students.